Mathematical modelling of energy wastage in absence of levelling and sectoring in wireless sensor networks. (2017) - Sharma, Priyanka; Murthy, Garimella Rama; Chilamkurti, Naveen
In this paper, we quantitatively reason the energy savings achieved by the levelling and sectoring protocol. Due to the energy constraints on the sensor nodes (in terms of supply of energy), energy awareness has become crucial in networking protocol stack. The understanding of routing protocols along with energy awareness in a network would help in energy optimisation with efficient routing. We provide analytical modelling of the energy wastage in the absence of levelling and sectoring protocol by considering network in the form of binary tree, nested tree and Q-ary tree. The simulation results reflect the energy wastage in the absence of levelling and sectoring-based hybrid protocol.